2017
DOI: 10.1002/art.40323
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase IIb Study of Mavrilimumab and Golimumab in Rheumatoid Arthritis

Abstract: ObjectiveThis 24‐week, phase IIb, double‐blind study was undertaken to evaluate the efficacy and safety of mavrilimumab (a monoclonal antibody to granulocyte–macrophage colony‐stimulating factor receptor α) and golimumab (a monoclonal antibody to tumor necrosis factor [anti‐TNF]) in patients with rheumatoid arthritis (RA) who have had an inadequate response to disease‐modifying antirheumatic drugs (DMARDs) (referred to as DMARD‐IR) and/or inadequate response to other anti‐TNF agents (referred to as anti‐TNF–IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 29 publications
2
66
0
Order By: Relevance
“…GM‐CSF has been implicated in RA pathogenesis and considered as a potential therapeutic target because GM‐CSF is abundant in the synovial fluid of RA patients and associated with activation of synovial macrophages to produce high levels of IL‐6 and TNF‐α in severe inflammation . Several clinical trials using GM‐CSF inhibition therapy for RA patients have indeed succeeded in dampening chronic inflammation with considerably high efficacy …”
Section: Th17 Cell–dependent Chronic Autoimmune Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…GM‐CSF has been implicated in RA pathogenesis and considered as a potential therapeutic target because GM‐CSF is abundant in the synovial fluid of RA patients and associated with activation of synovial macrophages to produce high levels of IL‐6 and TNF‐α in severe inflammation . Several clinical trials using GM‐CSF inhibition therapy for RA patients have indeed succeeded in dampening chronic inflammation with considerably high efficacy …”
Section: Th17 Cell–dependent Chronic Autoimmune Arthritismentioning
confidence: 99%
“…89,90 Several clinical trials using GM-CSF inhibition therapy for RA patients have indeed succeeded in dampening chronic inflammation with considerably high efficacy. [91][92][93][94] Our recent study with SKG mice has addressed which GM-CSF-producing cells are critical for arthritis development and how GM-CSF production is regulated in each population. Effector…”
Section: Gm-csf As a Key Cytokine Orchestrating Chronic Arthritismentioning
confidence: 99%
“…Several interesting differences in monocyte signaling were identified between RA and healthy controls. The observation that there is decreased responsiveness of monocytes to stimulation with GM-CSF, and the bimodal response in this cell population (Figure 3 and 4), are of particular interest given the initial success of anti-GM-CSF mavrilimumab in clinical trials of RA ( 31 ). GM-CSF is an inflammatory cytokine with strong activities cross myeloid cells populations, including DCs, macrophages, and monocytes.…”
Section: Discussionmentioning
confidence: 96%
“…A subsequent phase IIb trial (EARTH EXPLORER 1), demonstrated that mavrilimumab represented a rapid, effective and well‐tolerated potential treatment for RA patients who had previously failed treatment with conventional disease‐modifying anti‐rheumatic drugs (DMARDs), and even biologicals (anti‐cytokine therapies) targeting other inflammatory pathways , and this emphasized an important pathogenic role for the GM‐CSF axis in difficult‐to‐treat RA. Subsequently, results from the EARTH EXPLORER 2 trial confirmed that mavrilimumab was efficacious and well‐tolerated in RA patients who were inadequate responders to both conventional DMARDs and TNF‐inhibitors . Moreover, a subanalysis of the EARTH EXPLORER 2 trial, conducted to dissect whether mavrilimumab and golimumab (TNF inhibitor) in both conventional DMARDs and TNF‐inhibitor inadequate responder RA patients may differ in the modulation of peripheral biomarkers and pathophysiological pathways, showed that serum levels of CCL22 and CCL17 were suppressed selectively by mavrilimumab but not golimumab, while CXCL13 and ICAM1 levels were suppressed by golimumab but not mavrilimumab.…”
Section: Novel Therapies Targeting Myeloid Cell Relevant Anti‐inflammmentioning
confidence: 99%